Development of Interactive Electronic Module (E-Modul) Subject Ecosystem Based on I-Spring Application on Class X Senior High School - Ahmad, Ammar Faris; Daud, Firdaus; Palennari, Muhiddin (Biology Teaching and Learning, 2024)
Technological developments and the era of digitalization in the 21st century demand innovation in education, especially in the development of learning media, which is the basis behind this research. This research aims to develop an interactive e-module with ecosystem material based on the I-Spring application for class X SMA Negeri 5 Gowa which is valid and practical. This type of research is Research and Development (R&D) with the ADDIE development model which consists of five stages, namely analysis, design, development, implementation and evaluation. The research subjects were biology subject teachers and class X students at SMA Negeri 5 Gowa. Data was collected through e-module validation sheets and teacher and student response questionnaires. The validity of the emodule was measured with a validity percentage of 4.39, while practicality was measured through the responses of teachers (91.45%) and students (88.81%), both of which indicated the very practical category.Keywords: E-module, R&D, ADDIE, Valid, Practical.